Experimental determination and sensitivity analysis of the fatigue critical distance obtained with rounded V-notched specimens. (August 2018) - Santus, C.; Taylor, D.; Benedetti, M.
Highlights: Determination of experimental critical distances with rounded V-notched specimens. Comparisons between Line and Point Method and crack threshold critical distances. Assessment accuracy of blunt specimen obtained with sharper specimen derived length. Analysis of the fatigue data scatter effect on the critical distance determination. Critical distance inverse search extended to the fatigue finite life regime. Abstract: The critical distance inverse search procedure, recently proposed by the authors (Santus et al., 2018), was experimentally applied in this work to 42CrMo4+QT steel and 7075-T6 aluminium alloy for fatigue load ratios R = −1 and R = 0.1. The inverse search lengths were in good agreement with the critical distances derived from the crack threshold. The Point Method lengths were higher than the Line Method values since the relatively low stress distribution second derivative. However, this difference is compensated for when the corresponding Method, Point or Line, is then used for the fatigue strength assessment of another specimen or a component. The fatigue predictions and comparisons with the experiments are reported in an accuracy chart, showing that a small radius notched specimen is recommended to determine the critical distance and thus obtain an accurate strength assessment of a blunter specimen. This critical distance determination was then extended to the fatigue finite life, again obtaining accurate predictions, especially for the aluminium alloy. The online version of this paper is provided with MATLAB scripts which contain examples for the critical distance inverse search and the direct problem for the fatigue stress concentration factor calculation.